Symptomatic retention of the patency capsule: a multicenter real life case series - Kopylov, Uri; Nemeth, Artur; Cebrian, Alba; Wurm Johansson, Gabriele; Thorlacius, Henrik; Fernandez-Urien Sainz, Ignacio; Koulaouzidis, Anastasios; Eliakim, Rami; Toth, Ervin (Endoscopy International Open, 2016)
Background and aims: The patency capsule is designed to evaluate the patency of the small bowel before administration of small-bowel capsule endoscopy (SBCE) in patients at high risk of retention. The utilization of a patency capsule may be associated with a risk of symptomatic retention, but very few cases have been reported to date. The aim of our study was to describe our experience with this rare complication of a patency capsule.Methods: This was a multicenter retrospective case series. The medical records of patients who underwent a patency capsule test were scanned and all cases of symptomatic retention were collected.Results: In total, 20 symptomatic cases of retention out of 1615 (1.2 %) patency capsule tests were identified; in one patient, the patency capsule was retained in the esophagus, in the rest, the capsule was detected in the small bowel resulting in abdominal pain or small-bowel obstruction. One patient (5 %) required surgery; all other patients resolved spontaneously or after corticosteroid therapy.Conclusions: Symptomatic patency capsule retention is a very rare complication with a favorable prognosis. It should be recognized but its use in patients with suspected small-bowel stenosis should not be discouraged.